Kontribusi Manajemen Mutu Terpadu Terhadap Kinerja Guru dalam Pembelajaran - Rafiuddin (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
The performance of teachers in learning is a In general result of work accomplished by the teacher in carrying out the tasks assigned to him based on skills, experience and sincerity as well as the time available. Work performance is a combination of three important factors namely, the ability and interest of a worker, ability and acceptance of the explanation of the delegation of tasks, and roles and level of motivation of a worker. Teachers' professional attitudes, skills and experience that teachers have a considerable influence on the performance of teachers in the learning. Integrated quality management as an approach to doing business that seeks to maximize its competitiveness through continuous improvement of products, services, people, processes and organizational environments. The approach in the teaching experience of teachers have contributed to the performance of teachers in learning. Teachers who have long worked, tend to have more teaching experience in carrying out tasks on learning. Stock of knowledge, skills, skills and experience of the teacher will direct him in performing the task so well that teacher professional attitude has contributed significantly to the performance of teachers to have a positive attitude on the job, is concerned tend to have better performance.